Developing a formula for the comparison of athletics performances across gender, age and event boundaries based on South African standards - Bekker, S. W. J. (My University, 2018)
The author addressed the need of parents, school teachers and athletic coaches to be able to assess the level of performance and to compare performances of individual athletes of either gender and in any age group. This was achieved by creating formulas for the following areas in track and field athletics: • Correctly set base standards for all events from the results of 5 year weighted average performances. • Use the base standards to determine comparative standards for all events in all age groups. • Define a function to compare male and female performances in all events. • For all events, generate tables with a range from 0 to 1000 as a comparative measurement. These formulae were created using data from international and national meetings. Different case studies were used for each of the areas and the results were evaluated using the data. In all four areas, it was possible to define hybrid functions with a confidence factor better than 99%. The final performance tables can be updated during revision periods (every 2 to 4 years) by using the national results for the last 5 years. These revisions will be required as implements, tracks and training methods change with time and this will then in turn influence the performances. This is evident from the continuous improvement of records in all events. These tables will not only assist coaches to improve training techniques but it will also facilitate team managers to improve team selections, and it will open the options of meeting organizers to arrange meetings using different formats. As this is a new and unique formulation for measuring performances at junior level in world athletics it can be used as a basis for future improvements in the field of comparative measurement for athletics. Using these tables at senior level it may assist to settle arguments of performance comparisons that are not addressed by the current tables used by the International Amateur Athletics Federation (IAAF). It will also avoid the use of different tables for the same events in standard track and field athletics compared to those used for combined event competitions. The author of the tables used by the IAAF has recognised this work as a new and unique development. Future development will include the automatic update of all functions and creation of tables for publication from a standard Windows® based application. A companion application, using the results from this research, will be developed. This application will address all the administration functions required to conduct a meeting. It will include the preparation for the meeting, capturing of results during the meeting and result reporting after the meeting.
M. Tech (Department of Information and Communication Technology, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Athletics, Performance, Comparison, Measurement, Tables, Age groups, Events, Competitions; Athletics.; Olympics.; Sports -- Physiological aspects.